A face in the crowd [videorecording (DVD)] - Kazan, Elia; Kazan, Elia; Griffith, Andy, 1926-2012; Neal, Patricia, 1926-2010; Franciosa, Anthony, 1928-2006 (Criterion collection, 2019)
When a singing drifter is discovered on a radio show, fame on television follows along with his self-destructive behavior.